Síntese e caracterização de complexos organometálicos de Rutênio (D) contendo ligantes N-N doadores placados na hidrogenação de arilcetonas - Ramos, Thiago dos Santos (2017)
Ruthenium-arene complexes are widely studied as homogeneous catalysts over the last years, especially in applications with polar bonds hydrogenation reactions. These ruthenium-arene complexes are promising in the reduction of polar C=O type bonds of arylketones. As a consequence of these studies the objective of this work was to apply a series of coordinated ruthenium-arene complexes to iminopyridine ligands in the reduction of ketones. Initially were synthesized and characterized six iminopyridines ligands N-N donor {N-(pyridine-2- methylene)aniline (Amp); 4-chloro-N-(pyridine-2-methylene)aniline (Clmp); 4-methyl-N- (pyridine-2-methylene)aniline (Memp); 4-tert-butyl-N-(pyridine-2-methylene)aniline (Tbmp); 2,6-diethyl-N-(pyridine-2-methylene)aniline (Diemp); 2,6-diisopropyl-N-(pyridine-2- methylene)aniline (Diipmp)} by the condensation reaction between an aniline ortho- orpara- substituted and 2-pyridinecarboxaldehyde in the presence of p-toluenesulfonic acid as catalyst. The binuclear ruthenium(II) complexes [RuCl(^-Cl){p-cym)]2 { p-cym = para- cymene} was using as the synthesis precursor to prepare six complexes of general formula [RuCl(p-cym)(N-N)]PF6. The ligands and complexes characterizations were performed using XH NMR, cyclic voltammetry, infrared vibrational spectroscopy, ultraviolet and visible electron spectroscopy, elemental analysis and molar conductivity. The structure of the complexes [RuCl(p-cym)(Dipimp)]PF6 and [RuCl(p-cym)(Memp)]PF6 were determined by single-crystal X-ray diffraction. The elemental analysis of the ligands and the complexes are according to the suggested chemical structure. The ionic molar conductivity for the solution complexes of acetonitrile and dichloromethane confirm that these are 1:1 electrolyte. The complexes presented an anode process close to 1.80 V, an irreversible process, which leads to the incoordination of the p-cym ligand and consequent in situ formation of complex solvates of the general formula [RuCl(N-N)(CH3CN)3]+ which have values of E1/2 near 1.1 V. 1H NMR spectra for the free ligands showed singlets and doublets close to 8.15-8.30 ppm and 8.50-8.73 ppm for the ligands series N-N, these chemical shifts are due to the carbon-bonded hydrogen core adjacent to the imine e pyridine nitrogens. The complexes also showed the presence of theses chemical shifts a little more deshielding, confirming the ligands N-N coordination. The presence of the p-cym ligand was confirmed by the chemical shifts of the hydrogen core of the isopropyl radical, which yields doublets close to 0.98-1.30 ppm and septets close to 2.30-3.15 ppm, which is related to the coupling of methyl with isopropyl hydrogen. The complexes presented good catalytic activity in hydrogen transfer reactions to reduce the substrates analyzed using isopropanol as a source of hydrogen and solvent, emphasizing the complexes [RuCl(p-cym)(Clmp)]PF6 and [RuQ(p-cym)(Memp)]PF6 which showed conversions above 80% and the lowest relative standard deviation value for the two substrates. Using these complexes, a kinetic study of the hydrogen transfer reactions was carried out, where it was possible to verify the dependence of the substrate conversion on the temperature change. It was also determined the thermodynamic parameters such as the free energy of Gibbs of activation (AG*), enthalpy of activation (A#*) and entropy of activation (AS*), correlating them with the reaction behavior of each complex.